Long-Term Efficacy of Guselkumab in an Adolescent Hidradenitis Suppurativa Patients: A Case Report - Martora F; Battista T; Potestio L; Portarapillo A; Tommasino N; Megna M (Clinical, Cosmetic and Investigational Dermatology, 2024)
Fabrizio Martora, Teresa Battista,* Luca Potestio,* Antonio Portarapillo, Nello Tommasino, Matteo Megna Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Napoli, Italy*These authors contributed equally to this workCorrespondence: Fabrizio Martora, Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Via Pansini 5, Napoli, 80131, Italy, Tel +39 081 7462457, Fax +39 081 7462442, Email fabriziomartora92@libero.itAbstract: Managing HS has long posed a significant challenge for dermatologists. Adalimumab stands as the sole biologic drug sanctioned for HS, receiving approval in 2015 as an anti-tumor necrosis factor (TNF)-α drug. Real-life evidence over the years has debated its efficacy, suggesting a success rate hovering around 70%. However, the variability in existing treatments and the chronic-recurrent nature of the condition make its treatment and management exceedingly challenging. Hence, identifying new therapeutic targets for HS in the future becomes imperative. Recently, on October 31, 2023, the FDA approved secukinumab for moderate-severe HS, marking a significant development. There has been substantial discourse on the potential of anti-interleukin-23 drugs as new therapeutic avenues for treating HS in recent years. Here, we report a case of 17-year-old man successfully treated with Guselkumab. The results were confirmed at week 52.Keywords: hidradenitis suppurativa, anti-IL23, guselkumab, adalimumab, secukinumab